Death at the door [large type] - Hart, Carolyn G. (Hart, Carolyn G. Death on demand series, 2014)
"Annie Darling--owner of the mystery bookstore, Death on Demand--prefers fictional crimes as opposed to the real things. But in one tragic week, two acts of violence shake the island community of Broward's Rock. First, a beloved doctor is found shot dead, seemingly by his own hand. Only days later, a local artist is arrested after his wife is found murdered, bludgeoned by her husband's sculpting mallet. Convinced her brother did not commit suicide, the doctor's sister turns to Annie and her husband, Max, for help. She has found a cryptic sketch her brother drew, linking him with the murdered woman. Did someone want them both out of the picture? With the police considering both cases as good as closed, it's up to Annie and Max to sort through a rogues' gallery of suspects to see if someone is trying to frame the artist. But if Annie isn't careful, she may find herself having her own brush with death.."--